Структура и цели программ технического развития контейнерных терминалов морских торговых портов - Онищенко, Светлана Петровна; Леонтьева, Анна Игоревна (НТУ "ХПИ", 2018)
Охарактеризовано требование сбалансированности технического развития контейнерных терминалов морских торговых портов. Установлены составляющие внутренней и внешней среды, требующие соблюдение условия баланса в техническом развитии. Системе целей программы технического развития поставлена в соответствие структура программы, которая отражает конкретный набор проектов. Соответствие установлено на уровне вклада каждого проекта в достижение целей. Проанализированы варианты технологической зависимости проектов программы технического развития на содержательном уровне и на уровне формирования продуктов проектов. Представленные результаты формируют базу для формализации процедуры отбора проектов в программу технического развития с учетом ее установленных свойств.

The main objective of the seaport container terminals technical development is established and the procedure for decomposition of this purpose is characterized. As the main purpose, the improving of competitiveness has been defined. The requirement of the balancing of the seaport container terminals technical development has been formulated. It is determined that the balance should be reflected in accordance with the demand structure (real and promising in the near future) of the terminal's production capabilities both in volume and structure. Balance should be achieved both within the component of the internal environment, related to the level of technical development, and between the internal and external environment. The goals of development are formulated in accordance with the requirement of balance. The system of objectives of the technical development programs is aligned with the structure of the program reflected a specific set of projects. This accordance is established at the level of the each project contribution to the achievement of the goals system. It is determined that the main types of the technical development projects products are the machinery (equipment) operated as part of the material and technical base; implemented technology (new, improved, innovative). The variants of technological dependence for the projects of the technical development program at the content level and at the level of the project product are analyzed. Three main possible variants of the program structure were identified in terms of the interrelation of projects: projects are not technologically interrelated; all projects are technologically interconnected; individual projects are interrelated. The presented results form the basis for formalizing the procedure of selecting projects to the technical development program, taking into account its established properties.
Structure and porpoises of the technical development programs for seaport container terminals
Keywords: технологическое развитие; декомпозиция целей; вклад проекта; сбалансированность; decomposition of goals; contribution of the project; balance.